(untitled) (Experimental biology, 2015)
On the ground of own experience in the work with herbal and plant-pathologic material the authors give the recommendations on the keeping of such objects for the scientific and educative purposes. Anything objects with low moisture substances there are proposed to keep in dry state with the exposition in 30-40% carbamide solution before the making of micro-preparations (for the clarity and eradicating of rigidness). Exclusively traditional conserving media of the ground of ethyl spirit and formaldehyde, the conserving compositions with high osmotic pressure(of salts or organic substances) and presence of additional conserving factors are proposed. Cathode ions of copper and zinc salts in the contents of conserving liquids provide firm fungicide and fungi-static effect. Several liquid media kept plant-pathologic objects during 10-12 years without deterioration and morphological changing.